Evaluasi Program Terpadu Pengendalian Malaria, Pelayanan Ibu Hamil dan Imunisasi di Kabupaten Hulu Sungai Selatan dan Kota Banjarbaru Provinsi Kalimantan Selatan - Hanifah Rogayah; Yodi Mahendradhata; Retna Siwi Padmawati (Jurnal Kebijakan Kesehatan Indonesia, 2015)
Background: To reduce child and maternal mortality, as well as mortality and morbidity of malaria, an integrated malaria control program along with antenatal care and immunization has been implemented through malaria screening and provision of LLIN to pregnant women and the provision of LLIN to children under five who received full immunization. Objective: The objective of this study is to evaluate integrated malaria control program in Hulu Sungai Selatan District and Banjarbaru City, South of Kalimantan Province by exploring input, process and output of the program. Method: The study uses evaluation formative approach using qualitative method with exploratory qualitative design. Data is collected through in-depth interviews, focus group discussion, checklist of observation and documents related to the integrated program. Data analysis was performed with the reduction and presentation of the data, visualization, conclusions, and verification that describe the input, process and output variabels relevant to integrated malaria control program. Result: The dominant challenges in the input are commodity, funds, as well as the organization of integrated programs. Implementation of the integrated program is not optimal in the form of policies, capacity building, QA, supervision, and recording and reporting. The integrated program did not achieve the intended output in terms of LLIN coverage for children under f ive as well as pregnant women ANC coverage (Trimester I and IV). Conclusion: The implementation of integrated malaria control program in general was relatively weak in terms of input, process and output. Adequate inputs and processes to strengthen the implementation of the integrated program are necessary, so it can be one of the exit strategies for malaria control in pregnant women and children under five. Latar Belakang: Dalam upaya menurunkan angka kematian ibu dan anak serta angka kesakitan dan kematian akibat malaria, telah dilaksanakan program terpadu pengendalian malaria, pelayanan ibu hamil dan imunisasi melalui skrining malaria dan pemberian kelambu berinsektisida pada ibu hamil serta pemberian kelambu pada balita yang mendapat imunisasi lengkap.Tujuan: Penelitian ini bertujuan untuk mengevaluasi program terpadu di Kabupaten Hulu Sungai Selatan dan Kota Banjarbaru Provinsi Kalimantan Selatan dengan mengeksplorasi input, proses dan output program. Metode: Penelitian ini merupakan penelitian evaluasi formatif, dengan metode kualitatif dan desain penelitian kualitatif eksploratif. Pengumpulan data dengan wawancara mendalam, diskusi kelompok terarah serta observasi dan checklist dokumentasi. Hasil: Tantangan yang paling besar dan dominan pada input adalah komoditi, dana, serta organisasi program terpadu. Belum optimalnya pelaksanaan proses program terpadu berupa kebijakan, capacity building, QA , supervisi, serta pencatatan dan pelaporan. Tidak tercapainya output program terpadu yaitu cakupan kelambu pada balita dan cakupan kunjungan ANC ibu hamil (K1 atau K4). Kesimpulan: Program terpadu pengendalian malaria, pelayanan kesehatan ibu hamil dan imunisasi belum optimal pada komponen input, proses dan output. Adekuatnya input dan proses dapat memperkuat pelaksanaan program terpadu, sehingga dapat menjadi salah satu exit strategi pengendalian malaria pada ibu hamil dan balita.